2008
DOI: 10.1194/jlr.m700580-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Xanthophylls are preferentially taken up compared with β-carotene by retinal cells via a SRBI-dependent mechanism*

Abstract: The purpose of this study was to investigate the mechanisms by which carotenoids [xanthophylls vs. bcarotene (b-C)] are taken up by retinal pigment epithelial (RPE) cells. The human RPE cell line, ARPE-19, was used. When ARPE-19 cells were fully differentiated (7-9 weeks), the xanthophylls lutein (LUT) and zeaxanthin (ZEA) were taken up by cells to an extent 2-fold higher than b-C (P , 0.05). At 9 weeks, cellular uptakes were 1.6, 2.5, and 3.2%, respectively, for b-C, LUT, and ZEA. Similar extents were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(126 citation statements)
references
References 44 publications
3
122
0
1
Order By: Relevance
“…SR-BI was proposed to form a hydrophobic channel along which cholesteryl esters migrate (37). Furthermore, mutants of the ninaD gene, a homolog of SR-BI in the fruit fly Drosophila melanogaster, was reported to affect carotenoid uptake in gut for visual chromophore synthesis (38 -40), and SR-BI was also implicated in cellular carotenoid absorption (41)(42)(43)(44). Therefore, we considered these two genes to be strong candidates for the C gene, and designated the gene nearer the SNP marker C-080419-R16 Cameo1 and the other Cameo2.…”
Section: Resultsmentioning
confidence: 99%
“…SR-BI was proposed to form a hydrophobic channel along which cholesteryl esters migrate (37). Furthermore, mutants of the ninaD gene, a homolog of SR-BI in the fruit fly Drosophila melanogaster, was reported to affect carotenoid uptake in gut for visual chromophore synthesis (38 -40), and SR-BI was also implicated in cellular carotenoid absorption (41)(42)(43)(44). Therefore, we considered these two genes to be strong candidates for the C gene, and designated the gene nearer the SNP marker C-080419-R16 Cameo1 and the other Cameo2.…”
Section: Resultsmentioning
confidence: 99%
“…RPE expresses functional receptors for both LDL (LDL-R) and HDL (scavenger receptor B-I, SRB-I) and takes up these plasma lipoproteins ( 109,(135)(136)(137)(138), likely for resupply of essential lipophilic nutrients and cellular constituents. LDL-derived cholesterol taken up by RPE partitions remarkably fast (within hours) into membranes of the neurosensory retina ( 109,139 ).…”
Section: The Barrier Hypothesis: Lipid Accumulation and Transport Thrmentioning
confidence: 99%
“…Previous work in our laboratory (28,29) demonstrated that xanthophylls associated mostly with HDL, while -cryptoxanthin, lycopene, and -carotene predominantly associated with LDL in human serum. We also showed that zeaxanthin delivered by detergent micelles to ARPE-19 cells is preferentially taken up via an SR-B1-dependent mechanism compared with -carotene (23). The current work was designed to extend those studies and to investigate in detail the uptake and metabolism of lutein, zeaxanthin, meso-zeaxanthin, and -carotene delivered in their physiologically relevant transport vehicles.…”
mentioning
confidence: 99%
“…Differentiated ARPE-19 cells are often used as a model for the study of retinal metabolism because they show structural and functional properties similar to the human RPE (20). ARPE-19 cells express lipoprotein receptors necessary for studying lipoprotein delivery of carotenoids, including scavenger receptor class B1 (SR-B1), SR-B2, LDL receptor (LDLR), lipid transporters cluster determinant 36 (CD-36), and ABCA1 (21)(22)(23)(24)(25)(26)(27). Based on analysis of the expression of lipoprotein transporters and receptors in the retina and two different RPE cell lines, including ARPE-19 cells, it was proposed that circulating LDL and HDL enter the basolateral side of the RPE via the LDLR and SR-B1 (27).…”
mentioning
confidence: 99%